Gender Inequality in Screenwriting Work - Wreyford, Natalie (Springer International Publishing, 2018)
This is the first book to critically examine the recruitment and working practices of screenwriters. Drawing on interviews with screenwriters and those that employ them, Natalie Wreyford provides a deep and detailed understanding of entrenched gender inequality in the UK film industry and answers the question: what is preventing women from working as screenwriters? She considers how socialised recruitment and gendered taste result in exclusion, and uncovers subtle forms of sexism that cause women's stories and voices to be discounted.Gender Inequality in Screenwriting Work also reveals the hidden labour market of the UK film industry, built on personal connections, homophily and the myth of meritocracy. It is essential reading for students and scholars of gender, creative industries, film and cultural studies, as well as anyone who wants to understand why women remain excluded from many key roles in filmmaking.